The analysis of short supply chain patterns in urban vegetable stalls and its contributions to sustainable development goals - Ivana Arviani Tan; Rustina Untari (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: The long supply chain of the global food system faces criticism of poverty, which has led to the emergence of short supply chains (SSC) as an alternative. The urban system, particularly in Semarang City, still needs improvement because currently, food is still supplied from agricultural areas outside the city due to the city's inadequate conditions for farmed food. This study investigates the implementation of SSC through emerging urban vegetable stalls (